Identifikasi Argumentasi Ilmiah Siswa Topik Gelombang Bunyi dan Cahaya - Tomy Suganda; Parno Parno; Sunaryono Sunaryono (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: Scientific argumentation helps develop the skills needed in the 21st century, namely the ability to think critically and communicate effectively. The identification of the ability to argue scientifically can be a guide in developing learning. This research is a descriptive study that aims to describe the phenomenon of students' scientific arguments about the material of sound and light waves. This study involved 88 class XII students of SMA Negeri 1 Putussibau for the academic year 2020/2021 as research subjects. The instrument used in the form of 3 essay questions is the Scientific Argumentation Ability Test with a reliability of 0.622. Students' answers were analyzed based on the Toulmin Argumentation Pattern (TAP) level of argumentation. The results showed that the scientific argumentation of students on the topic of waves was still low, with the average level of student ability at levels 1 and 2. It was necessary to make efforts to improve students' scientific arguments, one of which was the application of the Argument Driven Inquiry learning model.Abstrak: Argumentasi ilmiah membantu pengembangan kemampuan yang diperlukan di abad-21, yaitu kemampuan berpikir kritis dan berkomunikasi efektif. Adanya indentifikasi kemampuan berargumentasi ilmiah dapat menjadi panduan dalam mengembangan pembelajaran.  Penelitian ini merupakan penelitian deskriptif yang bertujuan mengambarkan fenomena argumentasi ilmiah siswa pada materi gelombang bunyi dan cahaya. Penelitian ini melibatkan 88 siswa kelas XII SMA Negeri 1 Putussibau tahun ajaran 2020/2021 sebagai subyek penelitian. Instrumen yang digunakan berupa 3 butir soal esay Tes Kemampuan Argumentasi Ilmiah dengan reliabilitas 0,622. Jawaban siswa dianalisis berdasarkan level argumentasi Toulmin Argumentation Pattern (TAP). Hasil penelitian menunjukkan bahwa agumentasi ilmiah siswa pada topik gelombang masih rendah dengan level kemampuan siswa rata-rata berada pada level 1 dan 2. Perlu adanya upaya yang dilakukan untuk meningkatkan argumentasi ilmiah siswa salah satunya melalui penerapan model pembelajaran Argument Driven Inquiry.